Crystal, Solution and In silico Structural Studies of Dihydrodipicolinate Synthase from the Common Grapevine - Atkinson, Sarah C. (Public Library of Science, 2012)
Dihydrodipicolinate synthase (DHDPS) catalyzes the rate limiting step in lysine biosynthesis in bacteria and plants. The structure of DHDPS has been determined from several bacterial species and shown in most cases to form a homotetramer or dimer of dimers. However, only one plant DHDPS structure has been determined to date from the wild tobacco species, Nicotiana sylvestris (Blickling et al. (1997) J. Mol. Biol. 274, 608–621). Whilst N. sylvestris DHDPS also forms a homotetramer, the plant enzyme adopts a ‘back-to-back’ dimer of dimers compared to the ‘head-to-head’ architecture observed for bacterial DHDPS tetramers. This raises the question of whether the alternative quaternary architecture observed for N. sylvestris DHDPS is common to all plant DHDPS enzymes. Here, we describe the structure of DHDPS from the grapevine plant, Vitis vinifera, and show using analytical ultracentrifugation, small-angle X-ray scattering and X-ray crystallography that V. vinifera DHDPS forms a ‘back-to-back’ homotetramer, consistent with N. sylvestris DHDPS. This study is the first to demonstrate using both crystal and solution state measurements that DHDPS from the grapevine plant adopts an alternative tetrameric architecture to the bacterial form, which is important for optimizing protein dynamics as suggested by molecular dynamics simulations reported in this study.